Economy Studies: A Guide to Rethinking Economics Education - Sam de Muijnck; Joris Tieleman (Amsterdam University Press, 2021)
The Economy Studies project emerged from the worldwide movement to modernise economics education, spurred on by the global financial crisis of 2008, the climate crisis, and the COVID-19 pandemic. It envisions a wide variety of economics graduates and specialists, equipped with a broad toolkit, enabling them to collectively understand and help tackle the issues the world faces today. This is a practical guide for (re-)designing economics courses and programs. Based on a clear conceptual framework and ten flexible building blocks, this handbook offers refreshing ideas and practical suggestions to stimulate student engagement and critical thinking across a wide range of courses. Key features Adapting Existing Courses: Plug-and-play suggestions to improve existing economics courses with attention to institutions, history, values and practical skills. Teaching materials: A guide through the rapidly growing range of innovative textbooks and other teaching materials. Example Courses and Curricula: How to design pluralist, real-world economics education within the practical limits of time and resources. The companion website, www.economystudies.com, contains a wealth of additional resources, such as tailor-made booklets for more specific audiences, additional teaching materials and links to plug-and-play syllabi and courses, and opportunities for workshops and exchange with other economics educators.
Keywords: 330; economics; education; pluralism; student movement; Wirtschaftsstudium; Wirtschaftspädagogik; Lehrmaterial; Hochschullehre; Lehrplan